Nutrient harvest and soil fertility as influenced by legume-wheat (Triticum aestivum) sequences - PRASAD, N K; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993-95 to assess the contribution of preceding legume crop on succeeding wheat (Triticum aesfivum L. emend. Fiori & Paol) for crop production, nutrient harvest and balance of the same in soil under recommended doses of nutrients of khari crops and variable levels of nitrogen to succeeding wheat. Blackgram (phaseolus mango L.) as a preceding crop to wheat resulted in the maximum wheat production while stylo (Stylosanthes hamata L.) - wheat sequence accounted for higher wheat equivalent yield. Application of 75 kg N/ha to wheat grown after legume was as good as to wheat yield received at 100 kg N/ha after legume. Soybean (Glycine max (L.) Merr.)wheat sequence has removed the maximum quantity of N while wlieat grown after blackgram harvested the maximum quantity of N. Soybean - wheat sequence further removed the highest quantity of P but stylo - wheat sequence recorded the maximum recovery of K. Though all the legume - wheat sequences have recorded better build up in soil N, however, wheat grown after blackgram at 100 kg N/ha recorded the maximum build up in available soil N while wheat grown in absence of external N has left over maximum available P in soil. General increase in available K was noticed under all the sequences to their initial status.